Pediatric Cytopathology : A Practical Guide - Monaco, Sara E.; Teot, Lisa A. (Springer Berlin Heidelberg : Imprint: Springer, 2017)
This text presents serious challenges for trainees, clinicians, and practicing pathologists and cytopathologists due to the wide spectrum of diagnoses that may be seen in children and the lack of familiarity with these entities. This reference book has been designed as a practical, high-yield review of pediatric cytopathology. Key findings are highlighted and up-to-date information is provided on the diagnosis of pediatric lesions by cytology, with extensive guidance on differential diagnosis. The book includes tables and full-color images of the cytomorphology and ancillary studies, as well as pertinent histological correlation and guidance on technical issues. Pediatric Cytopathology: A Practical Guide will be an essential reference for anyone interested in the cytomorphological findings in childhood diseases.
Keywords: Medicine.; Oncology.; Pathology.; Pediatrics.; elektronické knihy; electronic books